Modifikasi Perilaku Anak Usia Dini: Problematika Anak ADHD - Abdul Latif, Muhammad; Kusumawardani, Nurfadilla; Ayuni, Nurul; Margareta Sukma A, Tiara; Febriayanti, Husnul (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
Behavior that often becomes a problem in children with ADHD is usually impulsive behavior. This behavior can be interpreted as actions done beyond the child's control. Consequently, this can result in children with ADHD being frequently avoided by their peers. This research aims to understand the behavior of each child with special needs, particularly those with ADHD. This study employs a qualitative research method. Data collection in the field is conducted through observation and interviews. Qualitative data analysis can be carried out through three simultaneous activities: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the first child has predominantly inattentive ADHD. This child has difficulty paying attention to details, such as being unable to focus while studying at school or doing homework, leading to frequent changes in schools and eventually dropping out. Meanwhile, the second child has predominantly hyperactive-impulsive ADHD. This child finds it difficult to sit still for long periods. As a result, this child is always supervised by their parents and only roams around the home environment.